Asymptomatic facial deformity resulting from a nasoalveolar cyst. Case report - Barbieri , Melina (2025)
Nasoalveolar cysts are rare non-odontogenic cysts that are commonly seen in the area of the wing of the nose. They are usually asymptomatic and the patient usually comes to the clinic for aesthetic/cosmetic reasons. Several treatment modalities have been described for the management of this lesion, the most used being excision and marsupialization. In this article we present the clinical situation of a patient where she manifests nasal deviation and swelling at the bottom of the vestibular sulcus above the upper anterior teeth of sector 2. A cystectomy is performed and the excised tooth is sent to pathology. There are many options for surgical management, such as endoscopic marsupialization, surgical excision, incision and drainage, injection of sclerotic agents, aspiration and cauterization. Although magnetic resonance imaging offers excellent visualization of soft tissues, computed tomography is less expensive. Ultrasound can also be useful and is a minimally invasive technique. Excision (cystectomy) is recommended whenever there is no risk of damaging anatomical structures, and marsupialization when the pathological entity has displaced teeth.